Organomercury oligonucleotide conjugates as artificial ribonucleases - Saleh Lange.Y.; Ora Mikko; Lönnberg Tuomas (Elsevier Inc., 2025)
Two oligonucleotide conjugates sharing the same sequence but incorporating a different 5′-terminal organometallic moiety were synthesized, by either direct mercuration in solution or oximation with an organomercury aldehyde on solid support. The potential of these conjugates to serve as new type of artificial ribonucleases was tested with a complementary 2´-O-methyl-RNA target sequence featuring a single cleavable RNA phosphodiester linkage. Both organomercury oligonucleotides greatly outperformed their metal-free counterparts as well as the previously reported small molecule organomercury RNA cleaving agent in catalytic activity, providing an important proof-of-concept. Compared to state-of-the-art metal-dependent artificial ribonucleases, however, the observed activity was modest.